Research methods in physical activity and health - Bird, Stephen R. (Routledge, Taylor & Francis Group, 2019)
Physical activity is a vital tool in preventing disease and managing recovery at a population level, with governments and health authorities relying on high-quality, university research into the risks associated with sedentary behaviour, optimal exercise prescription and effective lifestyle change to set and administer guidelines. Research Methods in Physical Activity and Health is the first book to comprehensively present the issues associated with physical activity and health research and introduce students and researchers to the methods available.